THE ROLE OF PERCEIVED VALUE AND PERCEIVED PRICE TO INFLUENCE CUSTOMER SATISFACTION AND CUSTOMER LOYALTY AT PT BANK SULUT - Tampi, Rebeca V. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2013)
Customer satisfaction in service industry is the basic reason that the performance of the industry already has attention from the people that already use the service. In bank, customer satisfaction becomes important to know what the customer need and want, to become loyal. Because, customer satisfaction is the first step, to make customer continuous use the service of the bank. This research is aimed to analyze the influence of perceived value and perceived price to customer satisfaction, perceived value and perceived price to customer loyalty and customer satisfaction to customer loyalty. Theories supporting research are perceived value, perceived price, customer satisfaction and customer loyalty. This study was conducted at PT. Bank Sulut central office which took 100 respondents from PT. Bank Sulut’s customer. The sample will be made random, in order to get results quickly and efficiently obtain the information needed in this research. This research using Path Analysis Method, where previous test validity, reliability, and classical assumption. And the conclusion are; perceived value and perceived price positive significant influence to customer satisfaction; perceived value has no positive significant to customer loyalty; perceived price has positive significant influence to customer loyalty, and customer satisfaction has positive significant influence to customer loyalty. Keywords: perceived value, perceived price, customer satisfaction, customer loyalty